The Dilemma of Dual Heritage: Nationality Selection among Japanese-Singaporean Multinational Children - Matsumura, Kayoko; Paidi, Rohayati; Somiah, Vilashini (WILAYAH: The International Journal of East Asian Studies, 2025)
In this study, we examined which significant factors influence the nationality choice of Japanese children who are also multinational backgrounds. With 3.5 out of every 100 couples being intermarried; the number of multinational children is steadily increasing. A significant number of Japanese multinational children have expressed concern about their nationality due to Japan’s concept of the one-person-one-nationality law. However, there is a limited number of research that have investigated nationality choices and their ensuing impact. To address this gap, this study applies a qualitative approach, conducting interviews with individuals who had already selected their nationality in which we focused on (1) language influences, (2) environmental factors, and (3) family impacts. The survey led to the following findings: (1) the language spoken at home had a stronger influence on nationality choice; (2) although the environment and upbringing had no direct relation to nationality choice, they did have an impact on the individual’s identity formation; and (3) the mother’s perspectives on nationality selection and the father’s role as both husband and father in the home has had an impact. It is vital to realise that there are instances in which Japanese who have other roots but live in Japan and speak Japanese struggle to establish a Japanese identity and to consider how those people may develop a Japanese identity.